Development Of Smart Greenhouse Farming Based On Internet Of Things - Andria Karina, Nerissa; Ahgalya Subbiah, Dr. (International Journal of Science, Technology & Management, 2024)
This project aim is to develop smart greenhouse farming based on IoT system for monitoring the quality for the plant which use sensor and Node-RED as a website for monitoring. The monitoring system using microcontroller such as humidity sensor,soil moisture to control the condition of soil moisture level. The phenomenon of greenhouse plants is particularly significant since it has the potential to help improve the economy and cut manufacturing costs. Given the agricultural industry's lack of human resources, one of the cultivation techniques that have to be improved is hydroponic plants, also known as greenhouse plants. Hydroponic plant technology can be used in conjunction with hydroponic plants. Tropical greenhouses have various advantages in plant cultivation as well as practical manufacturing potential.This technology can be utilized to apply according to plant demands to maximize yield in agriculture. The project employed is a tool for monitoring soil moisture that is based on a prototype using an online platform for monitoring humidity and plant quality, and it can assist farmers in decreasing the budget for production.